PENGARUH PRICE EARNING RATIO, LEVERAGE, DIVIDEND PAYOUT RATIO, PROFITABILITAS DAN CASH HOLDINGS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DALAM INDEKS LQ45 - Vicky Mabruroh; Riswan Riswan; Sri Lestari (Monex: Journal of Accounting Research, 2015)
The purpose of this study is to analyze the influence ofprice earning ratio, leverage, dividend payoutratio, profitability and cash holdings toward firm value. Study case on non-financial companies listed in theindex LQ 45 in the period 2010-2013. The populations is companies listed in the index LQ 45 on the IDX(Indonesia Stock Exchange). the method of the research is purposive sampling, there were 16 companies will beused as observation data. This study uses multiple regression analysis with SPSS (Statistical Package for theSocial Sciens) version 16. The results showed that dividend payout ratio not affect the firm value. Price earningratio, leverage and profitability has a positive effect on firm value. And cash holdings has a negative effect onfirm valueKeyword: firm value, price earning ratio, leverage, dividend payout ratio, profitability, cash holding